Sludge from stoneworking enterprises: prospects of using it as an additive in the ceramic industry - V.V. Korobiichuk; I.V. Leonets; V.I. Shamrai; V.V. Melnyk-Shamrai; A.O. Kryvoruchko (Технічна інженерія, 2025)
The paper examines the use of sludge, which forms during the processing of natural stone at stoneworking enterprises, as an additive for producing press powders used in the production of ceramic materials. Sludge is one of the waste products of the stoneworking industry, and its disposal is a pressing task in modern production conditions, as the waste volume is significant and negatively impacts the environment. At the same time, sludge can become a valuable additive to ceramic mixtures, as its physicochemical properties, particularly the granulometric composition, can improve the characteristics of the final products. The study focuses on the granulometric composition of sludge obtained at stoneworking enterprises using different stone processing technologies, including diamond-cable and disc machines. The analysis showed that the particle composition of the sludge varies significantly depending on the processing technology. In particular, when processing stone with diamond-cable machines, a larger number of medium-sized particles (0,1–0,2 mm) is formed, whereas disc machines produce coarser fractions (over 0,2 mm). This has a significant effect on the physicochemical properties of the sludge, and consequently, its ability to be used in ceramic production. It was found that sludge with larger fractions (> 0,2 mm) has a low compaction ability and worsens the strength characteristics of the final products, while smaller particles (< 0,1 mm) can improve the water resistance and other properties of materials. Moreover, it was established that not only the particle size but also characteristics such as particle shape and surface roughness affect the flowability and bulkiness of the powder, and consequently, the pressing process. The paper provides recommendations for potential ways to improve the quality of sludge for use in ceramic production, particularly through fraction separation and mechanical or gravitational separation of coarse particles. The importance of experimental studies to determine the optimal sludge content in ceramic mixtures is also justified, as the properties of the final products may significantly depend on the specific composition of the sludge. Thus, the results of the study confirm the possibility of effectively using sludge from stoneworking enterprises as an additive for ceramic materials, which will not only reduce the environmental impact but also enhance the economic efficiency of production. However, further research is needed to improve the sludge disposal technology and expand its use in the construction industry.